Internalization and Reflection of Sufism-Based Character Education Values from Syi’Ir Tanpo Waton - Soraya, Irma; Abitolkha, Amir Maliki; Imaniar, Fahmi (Didaktika Religia, 2023)
The formation of character represents the ultimate objective of education. However, the internalisation of character into social attitudes and behaviour continues to present a significant challenge. Pondok Pesantren Ahlus Shofa Wal Wafa in Sidoarjo has the potential to instill character traits through the use of Syi’ir Tanpo Waton, which has the capacity to influence the behaviour of students and congregation members. This study has two objectives. The first is to examine the process of internalising the values of character education expressed in Syi’ir Tanpo Waton within the Sufistic context of the language dauroh congregation. The second is to assess the reflection of these values and their impact on the Sufistic behaviour of the congregation. This qualitative research employs a multi-method approach, integrating a normative-manuscript and phenomenological perspective. The primary data were gathered from key informants, including the caregiver and principal of the Pondok Pesantren. The findings indicated that the internalisation process was facilitated by active participation and routine engagement in the activities of the pesantren and its foundation organisation. The values of character education were reflected in both concrete and abstract behaviours exhibited by the congregation